PENGARUH BRAND IMAGE DAN KUALITAS LAYANAN TERHADAP KEPUASAN WISATAWAN KE SAVAYA BALI - Sri Mas Iswari, Diah; Dewi, NGAS.; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
This research aims to examine the influence of brand image and service quality on tourist satisfaction visiting Savaya Bali. The development of Savaya Bali as a tourist destination is the basis for this research. In this study, the focus in on both domestic and international tourists who have visited or are currently visiting Savaya Bali. The research employs an analytical technique that combines quantitative and qualitative approaches. The quantitative approach is conducted through the distribution of questionnaires to 100 respondents, processed using SPPS ver. 29 for Windows, and ultizing methods such as reability tests, validity tests, classical assumption tests, t-tests, F-tests, multiple linear regression analysis, and determination coefficient tests, the variables used in this research are Brand Image (X1) and Service Quality (X2) as independent variables, and Satisfaction (Y) as the dependent variable. The results of this research show that brand image (X1) and service quality (X2) have a positive and significant influence on the satisfaction (Y) of tourists visiting Savaya Bali.